Physical and Mechanical Properties of 10-Year Old Superior and Conventional Teak Planted in Randublatung Central Java Indonesia - Fanny Hidayati; Joko Sulistyo; Ganis Lukmandaru; Tomy Listyanto; Harry Praptoyo; Rini Pujiarti (Masyarakat Peneliti Kayu Indonesia, 2015)
Tree breeding program has been conducted in Indonesia in order to produce more productive teak trees. Recently, from this program, superior clones (clone source) of teak have been selected for the establishment of the wider plantations. These clones show a good performance on growth characteristics such as stem diameter and tree height. However, it is important to evaluate wood quality of selected superior teak. Physical (heartwood percentage, wood color, basic density, and shrinkage per 1% change in moisture content) and mechanical (static bending strength and compressive strength) properties were investigated for 10-year old of two sources type of teak (superior and conventional) planted in Randublatung, Central Java, Indonesia. There was not significant different between superior and conventional teak was found in all physical and mechanical properties of both teak wood, suggesting that wood properties of both teak are similar at the same age. All trees are in juvenile phase as show by increasing of basic density from pith to bark. Basic density has positively correlation with all mechanical properties measured. It can be said that basic density can be used to estimate mechanical properties.Keywords: conventional teak, mechanical properties, physical properties, superior teak